A MIXED SOLVENCY APPROACH TO IMPROVED FORMULATION DEVELOPMENT AND CHARACTERIZATION OF A RAPID-RELEASE NON-STEROIDAL ANTI-INFLAMMATORY DRUG - Anasuya Patil; Teasha Chakraborty; Shashi Upasana; Bapai Pal; Subhajit Bhunia; Lokesh Premchand Kothari; Uma Shanker Maurya; Konda V V S Krishna (The Bioscan, 2025)
The formulation development and characterization of rapid-release non-steroidal anti-inflammatory drugs (NSAIDs) via a mixed solvency approach represent a significant advancement in pharmaceutical science. This study investigates the utilization of mixed solvency concepts to enhance the solubility and dissolution rates of NSAIDs, thereby facilitating their rapid release. Through systematic optimization of formulation parameters, including solvent selection, co-solvency ratios, and surfactant concentrations, novel NSAID formulations with improved drug delivery profiles were developed. The characterized formulations were subjected to rigorous physicochemical analyses and in vitro dissolution studies to evaluate their performance. The results underscore the efficacy of the mixed solvency approach in achieving enhanced formulation development and rapid-release characteristics for NSAID drugs. By leveraging the synergistic effects of multiple solvents and surfactants, this approach offers a versatile and efficient strategy for overcoming drug solubility challenges and enhancing therapeutic efficacy. This research contributes to the advancement of pharmaceutical formulation science and holds promise for improving the efficacy and patient compliance of NSAID medications.